Strategic Analysis of Collaborative Governance for Disaster Management on Forest and Land Fires in Indonesia - Ruswandi, Dody; Sumartono; Maarif, Syamsul; Wijaya, Andy Fefta (International Journal of Criminology and Sociology, 2021)
This research aims to understand the strategic analysis of collaborative governance on forest and land fire disasters at the ontological and sociological level that are very significant in reducing risk of natural disasters in Indonesia. The problem is very interesting to be analyzed by conducting a descriptive qualitative research based on theory of public policy, collaborative governance, and strategic management. The data were collected through in-depth interview, observation, and related documentation in forest and land fire cases in Indonesia. The data were analyzed by using interactive models, which are data reduction, data display, data verification, and supported by triangulation. The results were based on ontological and sociological level by using collaborative governance perspective and strategic analysis of internal, external, supporting, and inhibiting factors for reducing disaster risks and improving disaster management. Vision and mission of public policies on disaster management are needed for improving and providing information to stakeholders regarding regulations and sanctions in natural disaster management and produce a revised relevant regulation for state agencies as public officials in making regulations on disaster management in Indonesia.